Reversible Properties of Monoid Crossed Products (Communications in Mathematical Research, 2020)
We study the reversible properties of monoid crossed products. The newclass of strongly CM-reversible rings is introduced and characterized. This class ofrings is a generalization of those of strongly reversible rings, skew strongly reversiblerings and strongly M-reversible rings. Some well-known results on this subject aregeneralized and extended.